Conversational analysis of doctor-patient exchanges / Badli Esham Ahmad - Ahmad, Badli Esham (Universiti Teknologi MARA Cawangan Pahang, 2002)
The study aims at analyzing the talk exchange between patients and doctor but is restricted to the general discussion and opening talk between the doctor and the patients. The study sets out to investigate if there exist any age and gender preference in the talk exchange. After careful analysis of the talk exchanges, it is safe to· say that there are differences in talk exchange tactics and strategies between the genders as well as age difference.